KARAKTERISTIK TANAH- TANAH VOLKAN MUDA DAN KESESUAIAN LAHANNYA UNTUK PERTANIAN DI HALMAHERA BARAT - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Abstract Land resource potential mapping at scale of 1:50,000 was conducted in West Halmahera Regency covering total area of 254,000 ha to suppqrt agricultural development planning. About 45% of the total area is the soils that developed from young volcanictufflash. The objective of the study are to characterize soil properties formed from young volcanic materials of the strato-volcanoes landforms, and to determine land suitability for annual and perennial crops. Ten representative soil profiles were studied in the field and 20 selected 5. oilsamples of A and 8 horizons from the soil profiles were analyzed their physical and chemical properties, and sand mineral composition in the laboratory. The results indicate that the soils have deep solum, dark colored, well drained, loam to sandy loam texture, weak angular blocky structure, and friable consistency that contribute to favorable soil tillage. The soil fertility status is moderately high reflected by slightly acid to neutral soil reaction (pH 6.0-6.8) with medium to high organic carbon content (2.56-7.39%), medium to high potential P20Scontent (0.19-0.55 g kg-1),low to high potential K~ content (0.08-0.85 g kg-1),low to high cation exchange capacity (14-30 cmol kg-1), and medium to high base satUration (45-100%). Sand mineral composition is dominated by high content of weatherable minerals with high nutrient reserve (58-81%). Land suitability of the soils are classified into highly to marginally suitable for annual and perennial crops, with limiting factors of high P retention that may need higher P fertilizer, and steep slopes which contribute to erosion hazard and landslide. Agricultural development for annual crops are directed to volcanicplain and lower slopes, while perennial crops are directed to middle slopes of the strato-volcanoes followed by applicationof soil conservation techniques. Keywords: land resource mapping, land suitability, volcanic materials, Halmahera island